2013
DOI: 10.1371/journal.pone.0084275
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Viral Reservoirs in Multiple Tissues after Antiretroviral Therapy Suppression in a Macaque RT-SHIV Model

Abstract: Although antiretroviral therapy (ART) can suppress HIV-1 replication sufficiently to eliminate measurable plasma viremia, infected cells remain and ensure viral recrudescence after discontinuation of ART. We used a macaque model of HIV-1/AIDS to evaluate the location of infected cells during ART. Twelve macaques were infected with RT-SHIVmne, a SIV containing HIV-1 reverse transcriptase, conferring sensitivity to non-nucleoside reverse transcriptase inhibitors (NNRTIs). Ten to fourteen weeks post-infection, 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 61 publications
(63 reference statements)
1
58
0
Order By: Relevance
“…Their regimen consisted of TFV, (Ϫ)-FTC, and raltegravir, initially for 1.5 months and then intensified with the protease inhibitor darunavir (pharmacokinetically enhanced by ritonavir) for 80 days and, lastly, reinforced with the addition of the CCR5 antagonist maraviroc (42). Likewise, Kline et al monitored RT-SHIV mne in rhesus macaques over 20 weeks and found persistence of viral reservoirs in lymphoid tissues, despite undetectable plasma viremia at the time of necropsy (43). Unfortunately, eradication was not achieved in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Their regimen consisted of TFV, (Ϫ)-FTC, and raltegravir, initially for 1.5 months and then intensified with the protease inhibitor darunavir (pharmacokinetically enhanced by ritonavir) for 80 days and, lastly, reinforced with the addition of the CCR5 antagonist maraviroc (42). Likewise, Kline et al monitored RT-SHIV mne in rhesus macaques over 20 weeks and found persistence of viral reservoirs in lymphoid tissues, despite undetectable plasma viremia at the time of necropsy (43). Unfortunately, eradication was not achieved in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was washed with isopropanol and ethanol and samples were suspended in 10 mM Tris-HCl (pH 8.0). Tissue vRNA isolation was performed as previously described (54).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative PCR was performed on cDNA using SsoFast probes SuperMix (Bio-Rad), SIVgag-F (5=-GTCTGCGTCATCTGGTGCATTC-3=) and SIVgag-R primers, and the SIVgag-probe (5=-FAM-CTTCCTCAGTGTGTTTCACTTTCTCTTCT-GCG-3= 6-carboxytetramethylrhodamine [TAMRA]). CCR5 primers and probe were previously described (54). Reaction conditions were 1 cycle of 95°C for 2 min followed by 45 cycles of 95°C for 15 s and 60°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…PCR was performed on cDNA corresponding to 50 ng RNA. Reaction condition: 5 min 94°C; 30 cycles of 90 s at specified annealing temperature, 90 s 72°C, 30 s 94°C; 5 min at specified annealing temperature and 10 min 72°C [14,15]. Primer sequences for analytical RT-PCR experiments, length of amplicons and annealing temperatures were as follows: PDFGR-α (5′-GACGAGACCATCGAGGACAT-3′, 5′-GCCTCGGGAACTTTCTCTCT-3′, 207 bp, 55°C); PDGF-B (5′-CTGAGCTGGAC TTGAACATGAC-3′, 5′-CGCACAATCTCAATCTTTCTCA-3′, 307 bp, 60°C); h-Actin (5′-ACATCCGCAAAGACCTGTAC-3′, 5′-GCCATGCCAATCTCATCTTG-3′, 346 bp, 58°C); m-Actin (5′-CTTTGCAGCT-CCTTCGTTG-3′, 5′-TGGTAAACAATGCCATGTTCA-3′, 274 bp, 58°C).…”
Section: Gene Expression Analysis Of Rfp Labeled Human Tumor Cells Anmentioning
confidence: 99%